Surgery paradigm for locally advanced breast cancer following neoadjuvant systemic therapy - Sun, Ziyue; Liu, Kexin; Guo, Yanru; Jiang, Nanyuan; Ye, Meina (Frontiers in Surgery, 2024)
Locally advanced breast cancer (LABC) remains a significant clinical challenge, particularly in developing countries. While neoadjuvant systemic therapy (NST) has improved the pathological complete response (pCR) rates, particularly in HER2-positive and triple-negative breast cancer patients, surgical management post-NST continues to evolve. The feasibility of omitting surgery and the increasing consideration of breast-conserving surgery, immediate reconstruction in LABC patients are important areas of exploration. Accurate assessment of tumor response to NST through advanced imaging and minimally invasive biopsies remains pivotal, though challenges persist in reliably predicting pCR. Additionally, axillary lymph node management continues to evolve, with emerging strategies aiming to minimize the extent of surgery in patients who achieve nodal downstaging post-NST. Minimizing axillary lymph node dissection in favor of less invasive approaches is gaining attention, though further evidence is needed to establish its oncological safety. The potential for personalized treatment approaches, reducing surgical morbidity, and improving quality of life are key goals in managing LABC, while maintaining the priority of achieving favorable long-term outcomes.